Development and validation of a scale for the psychological determinants of dietary management behavior in hemodialysis patients during dialysis - Taofeng Wu; Yingying Jiang; Hongyun Yan; Jingfang Chen; Xianrong Xu; Xingxing Shen (PLoS ONE, 2026)
Objective This study aimed to develop and validate a scale for psychological determinants and behavioral performance of diet management behaviors in hemodialysis patients during dialysis sessions. Methods A preliminary item pool was generated based on the theory of planned behavior and evidence synthesis. The Delphi method, involving 19 experts, was employed to refine the scale content, resulting in an initial draft. Participants were recruited from four hemodialysis centers in Suzhou between 01/04/2024 and 31/05/2024. This draft was then administered to 418 hemodialysis patients from these centers. Data were analyzed using SPSS 25.0 and AMOS 13.0 for item analysis, reliability, and validity assessment. Results The response rate across two Delphi rounds was 100%. The expert authority coefficient was 0.88, and Kendall’s concordance coefficient for the second round was 0.245 (P < 0.05). The final scale comprised three dimensions (attitude, subjective norms, and perceived behavioral control) with 21 items. The overall Cronbach’s α was 0.964, with subscale α coefficients ranging from 0.918 to 0.938. Split-half reliability was 0.914, and test-retest reliability was 0.657. The scale-level content validity index (S-CVI) was 0.86, and item-level CVI (I-CVI) ranged from 0.800 to 1.000. Exploratory factor analysis extracted three common factors, accounting for 77.447% of the cumulative variance. Confirmatory factor analysis showed an acceptable marginal model fit after residual error modification. Conclusion The developed Diet Management Behavior Scale for Hemodialysis Patients demonstrates acceptable reliability and validity. Given the limitations of regional sampling and moderate expert consensus, the scale is preliminarily suitable for assessing psychological determinants of diet management and behavioral status during dialysis.